The Mayor of Batam Ex-Officio as Head of The Batam Concession Agency: Cross-Jurisdictional Authority and Legal Problems - Soerya Respationo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to explore the impact of granting the position of Head of the Batam Concession Agency to the Mayor of Batam on an ex-officio basis on the principle of "check and balance" in the governance of Batam and to assess the extent to which this policy is consistent with the principles of regional autonomy and decentralization, which are constitutional cornerstones in Indonesia. Through a normative legal research method using secondary data, this study reveals that the policy of granting ex-officio positions has a significant impact on the principle of "check and balance" with a potential reduction in the effectiveness of internal and external supervision, as well as an increased potential for abuse of power that may affect the integrity of decision-making. In addition, this policy raises essential questions about consistency with regional autonomy and decentralization principles, the main pillars of Indonesia's governance system. The principle of regional autonomy aims to give authority to local governments to manage their affairs without excessive interference from the central government. This research provides important insights into the consequences and consistency of government policies that may affect the fundamental principles of regional governance.